Human and Nature: Between Destruction and Creation - Gwiazdowicz, Dariusz J.; Janicki, Tadeusz (Studia Historiae Oeconomicae, 2024)
The problem of interaction between man and nature throughout history is, relatively, rarely addressed by classical historiography. The session entitled Man and Nature: Between destruction and creation, organized and chaired by Prof. Tadeusz Janicki (Faculty of History, UAM, Poznań, Poland) and Prof. Dariusz J. Gwiazdowicz (Department of Forest Protection, Poznań University of Life Sciences, Poland) on 24 August 2022 as part of the XXIII International Congress of Historical Sciences Poznań 2022, was an attempt to change this tendency and broaden the existing research perspective. The papers delivered during the occassion were the starting point for the preparation of a special issue of the journal Studia Historiae Oeconomicae (SHO), the primary purpose of which is interdisciplinary reflection by specialists from various scientific disciplines on the problem of destruction of natural landscapes and creation of cultural landscapes, along with other issues concerning the interaction between humans and the natural environment from prehistoric times to the present. This special issue of SHO consists of seven articles on diverse topics, analysing human interactions with nature through different historical periods, meanwhile taking into account their economic, civil, social and climatic conditions. The result is a multifaceted mosaic of topics that constitutes an original and interdisciplinary analysis of man’s relationship with nature, which may be a source of inspiration for readers and perhaps further research in this field.